“The Kids Nobel” Project as the platform for scientific knowledge popularization at modern scientific libraries - Ya. L. Shrayberg; E. N. Taran; E. V. Khoroshavina; Я. Л. Шрайберг; Е. Н. Таран; Е. В. Хорошавина (Scientific and Technical Libraries, 2023)
The National Library Association “Libraries of the Future” (NALF) supported through the RF Presidential Grant for Civil Society Development approved by the Presidential Grants Foundation, has been implementing the All-Russian Scientific and Educational Project “The Kids Nobel”. The Project main goals are to promote scientific knowledge and to engage 7–8 grade students in urban and rural settlements in research. At this stage, four pilot RF subjects are selected, namely Arkhangelsk, Kaluga, Ryazan and Saratov regions. Russian National Public Library for Science and Technology, today the country’s largest sci-tech library, and a NALF founder, is the main partner of “The Kids Nobel”. The All-Russian Scientific Educational Project “The Kids Nobel” is accomplished in two vectors: educational webinars for children in the main fields of the Nobel Prize, i. e. physics, chemistry, physiology, medicine, literature, politics (Nobel Peace Prize). Outstanding scientists, pedagogues, public officials, librarians deliver the lectures. The lecture course is followed by preparing and presenting students’ research works. The regional project curators, i. e. children’s school, universal, etc., libraries inform students on the events or use the course and workshop materials to organize their own events. The second vector is the contest of kids’ research projects in the fields of Nobel Prize. Under supervision of library curators, contest participants are to present their research work and findings through the Project website before July 1, 2023, one research work for a field, though several fields can be selected. Национальная библиотечная ассоциация «Библиотеки будущего» (НАББ) при поддержке гранта Президента Российской Федерации на развитие гражданского общества, предоставленного Фондом президентских грантов, реализует Всероссийский научно-познавательный проект «Детский Нобель». Основная задача проекта – популяризация научных знаний и вовлечение учеников 7–8 классов из городов и сельских поселений в исследовательскую ...